Pengaruh Penggunaan Media Video Animasi Audio Visual Agriculture Aeroponic Terhadap Peningkatan Minat Dan Hasil Belajar Gen – Z - Firdaus, Muhammad Rifki; Gayatri, Siwi; Hasfi, Nurul (Hasanuddin University, 2025)
This study investigates the declining interest of the younger generation in agricultural careers, despite agriculture’s vital role in national economic growth and food security. Generation Z, living in the digital era, tends to prefer technology-oriented fields rather than conventional agriculture. Therefore, this research examines the influence of audio-visual animated video media as an innovation in agricultural learning to increase students’ interest and learning outcomes. The study was conducted at SMK Negeri 1 Beringin, Deli Serdang Regency, which has strong potential to develop technology-based education but has not yet implemented direct agricultural learning. Using a Quasi-Experimental Design with a Nonequivalent Control Group model, the research involved 60 twelfth-grade students divided into experimental and control groups. Data were collected through pretests, posttests, and questionnaires, and analyzed using SPSS through validity, reliability, normality, and homogeneity tests, followed by simple linear regression, t-tests, and F-tests. The results show that the use of aeroponic agriculture audio-visual animated video media has a significant influence on increasing students’ interest and learning outcomes compared to conventional methods. The integration of visual and animated elements enhances engagement, clarifies complex agricultural concepts, and provides more interactive and contextual learning experiences. Overall, this study concludes that the use of audio-visual animated video media not only improves learning performance but also strengthens the image of agriculture as a modern, innovative, and technology-based field, supporting the regeneration of future farmers in the digital era. Keywords: agriculture, animated video, audio-visual media, learning outcomes, student interest